A 3D Creep Model considering Disturbance Damage and Creep Damage and Its Application in Tunnel Engineering. (21st April 2020) - Wang, Geng-Feng; Sun, Fan; Xiong, Xiao-Hui; He, Lei; Zhang, Ke-Hong
Abstract : Based on the Kachanov damage theory and elastic wave theory, considering the long-term creep damage from time dimension and instantaneous disturbance damage from space dimension, we presented a 3D damage creep model and converted it to difference expressions in order to write into the finite difference software FLAC 3D . Then, according to the results of creep tests, we conducted parameter inversion of our damage creep model with the help of the particle swarm optimization (PSO) method. Finally, the damage creep model was applied in a railway tunnel project in Yunnan to simulate the tunnel deformation. Compared with the Burgers model and the model considering only creep damage, our model which considers both creep damage and disturbance damage yielded more reasonable results.